An in vitro and in silico study of altered airway smooth muscle structure and function in a remodelled asthmatic airway - Brown, Sarah (2023)
Inflammatory processes in the airway lead to altered extracellular matrix (ECM) and increased airway smooth muscle (ASM), which is responsible for the rapid contraction of asthmatic airways during exacerbations. Increased ASM contributes substantially to the thickening of airways (airway remodelling), and a higher likelihood of experiencing potentially fatal attacks. In culture, ASM cells exhibit changes in shape and contractile ability between a spindle-shaped contractile phenotype and a more rounded proliferative phenotype with synthetic properties capable of depositing ECM. The link between phenotype switching and corresponding changes in structure, function and relative bio-mechanical abilities in vivo is unclear, but key in understanding remodelling. The aim of this project is to combine in silico and in vitro techniques in order to develop models that contribute to the identification of key mechanisms involved in airway remodelling and provide a framework for predicting dynamic mechanical changes in airway tissue.